The effect of fundamental and technical variables on stock price (Study on manufacturing companies listed in Indonesia Stock Exchange) - Eva Dwi Astutik; Surachman Surachman; Atim Djazuli (Universitas Hayam Wuruk Perbanas, 2014)
A capital market is any trade in securities which are called stock exchanges. In the capital market, the sellers and buyers meet in order to raise capital. More specifically, stock price used by investors is one of the important information before deciding investment. Therefore, the investors must have guidelines when investing to be done. This study aims to analyze the effect of fundamental and technical variables on stock prices. The variables used in this study are Debt Equity Ratio (DER), Return On Equity (ROE), Price Earnings Ratio (PER), Interest Rates (IR), and Exchange Rates (ER). Data analysis was performed on 45 manufacturing companies listed in Indonesia stock Exchange during 2007-2011 by using multiple analysis regression. The results showed that Return on Equity, Price Earnings Ratio and Exchange Rate have positive effect to stock prices, but Debt to Equity Ratio and Interest Rates has no effect on stock prices. The practical implication is that in determining stock prices not only from the company's internal factors, but also from external companies.